Social representation of Hansen's disease thirty years after the term 'leprosy' was replaced in Brazil - Oliveira Maria Leide Wand-del-Rey de; Mendes Carla Maria; Tardin Rachel Tebaldi; Cunha Mônica Duarte; Arruda Angela (História, Ciências, Saúde: Manguinhos)
Based on the theories of social representation (SC) and Central Core (CC), a structural study was undertaken regarding the neologism hanseníase (Hansen's disease), the term adopted by Brazil's Ministry of Health in the 1970s. Carried out during 2001, this study interviewed eight hundred housewives residing in the Rio de Janeiro and Duque de Caxias municipalities. It found that Hansen's disease is part of a process of modernization of common thinking, anchored in the traditional representation of leprosy. This finding is understandable from the perspective that the central structure of a social representation has a historical determination, so short- and middle-term changes are not to be expected. Furthermore, there has been no ongoing investment in social marketing to make the new terminology more widely known. The authors discuss the relation between social representation and the concept of the history of mentalities.